Perkembangan Penelitian dan Pemetaan Topik pada Riset Sapi Bali berdasarkan Publikasi Jurnal Ilmiah dan Prosiding - Abdul Rahman Saleh; Sri Rahayu; Jakaria Jakaria (Perpustakaan Nasional, 2023)
Animals that have the potential to produce meat that can be developed are Bali cattle. Unlike imported cattle, Bali cattle are superior because they can withstand all weather and adapt easily. Research on Bali cattle is quite a lot. However, we do not yet know the direction and status of the research. For this reason, it is necessary to conduct a study of the research that has been carried out. The research data comes from secondary data, namely scientific journal articles and proceedings articles. Data publication year is limited to June 2023. Data is tracked using Publish or Perish software. The data obtained was processed using Zotero, MS-Excel and VOSviewer software. There were 983 studies found, with the highest number of animal feed and nutrition, with 190 studies (19.31%). The most productive researcher is Jakaria (49 titles). The number of Bali cattle studies each year varies greatly with the highest number occurring in 2020 (169 studies). It is known that the authorship pattern of the Bali cattle research results article is in accordance with Lotka's law with an exponent value of 2.1 and a constant value of 66%. The researcher collaboration map and research topic map were successfully created using VOSviewer. The degree of author collaboration was 0.91. Related research including animal waste, animal welfare, animal farm and conservation can still be developed because there are not many researches in these fields.